A Paper-Based Assay for the Determination of Total Antioxidant Capacity in Human Serum Samples - Michelle T. Tran; Sophia V. Gomez; Vera Alenicheva; Vincent T. Remcho (Biosensors, 2024)
Determining the total antioxidant capacity (TAC) of biological samples is a valuable approach to measuring health status under oxidative stress conditions, such as infertility and type 2 diabetes. The Trolox equivalent antioxidant capacity (TEAC) assay is the most common approach to evaluating TAC in biological matrices. This assay is typically performed in clinical settings on a microtiter plate using a plate reader. However, the instrumentation and expertise requirements, and the resulting delay in the reporting of assay outcomes, make solution-based TEAC assays impractical for point-of-care or at-home testing, where individuals may want to monitor their health status during treatment. This work introduces the first microfluidic paper-based analytical device (µPAD) that measures TAC in human serum using TEAC assay chemistry. TAC was determined through a colorimetric image analysis of the degree of decolorization of 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) radical cations (ABTS●+) by serum antioxidants. The µPAD showed a linear response to Trolox, ranging from 0.44 to 2.4 mM, (r  =  0.999). The performance of paper-based TEAC assays was validated through direct comparison to solution-based TEAC assays. There was a 0.04 mM difference in TAC values between the two platforms, well within one standard deviation of a standard solution-based assay conducted on an aliquot of the same serum sample (±0.25 mM). The µPAD had a limit of detection (LOD) of 0.20 mM, well below the TAC of normal human serum. The results suggest that the proposed device can be used for biological TAC determination and expands the field of TAC analysis in point-of-care health monitoring.